Diversidade e evolução da microbiota lática autóctone em queijo Muçarela de búfala e aplicação tecnológica dos isolados - Silva, Luana Faria [UNESP] (2015)
In Brazil, buffalo Mozzarella cheese has good acceptance by its consumers and growing market. However, there are few scientific data about autochthonous lactic acid bacteria (LAB) involved in traditional manufacturing processes of this product nationally. Thus, this study aimed to identify the autochthonous LAB isolated during the buffalo Mozzarella cheese manufacture and storage period, as well as to evaluate the evolution and dynamic of lactic microbiota and their technological characteristics and potential of industrial application. First, isolated one hundred fifty-two lactic cultures isolated from raw milk, curd, stretched curd, mozzarella cheese, and solution of maintenance after being produced and during storage were characterized by the ability to grow in different temperatures (15, 30 and 45 °C), pH (4.5 and 9.6) and concentrations of NaCl (4.0, 6.5 and 10.0%), as well as the ability to produce CO2 from glucose. The biodiversity and evolution of LAB were evaluated by 16S rRNA gene sequencing, RAPD-PCR, and RFLP-PCR techniques. Regarding the growth under different conditions, most of the strains grow well at 30 °C, are feasible in the presence of 6.5% NaCl, and in general, presented best growing in pH 9.6. The isolated LAB were identified as: Enterocccus faecalis, Lactococcus. garvieae, Lactobacillus helveticus, Lactococcus lactis, Streptococcus thermophilus, Leuconostoc citreum, Lactobacillus delbrueckii subsp. bulgaricus, Enterococcus sp., Lactobacillus fermentum, Lactobacillus casei and Leuconostoc mesenteroides. The RAPD-PCR technique allowed evaluating the dynamics of representative LAB in the different steps of Mozzarella production and storage period. Sixty clusters were obtained by RAPD-PCR. All cultures grouped by RAPD-PCR, which presented more than 85% of similarity (114 cultures), were assessed by RFLP-PCR. Most of the LAB was clustered with 100% similarity by RFLP-PCR technique...